Book prices and monetary issues in Renaissance Europe - Francesco Ammannati (JLIS.it, 2018)
The difficulties associated with the creation of a large database of book prices include giving effective answers to questions such as how prices were formed during the various steps of the production process (sedimentation of production costs, costs related to the sale) or what the nature of the assigned value is (estimated in the case of used books, or of stock inventories, or the result of special conditions offered to specific customers, etc.). But first it is necessary to reflect on the interpretation given to the figures provided by the heterogeneous documentation which supports the creation of such a database. The many reference currencies in which these prices are expressed, depending on the monetary area of action of the economic operators (printers, booksellers, customers) are likely to confuse and mislead if their exact meaning is not clearly understood. This problem becomes even more urgent when, for example, the primary sources are the private notes of a collector who recorded how much he had paid for a book, or when two different currencies in place or in time have the same name. This aspect is also crucial in comparing different places and markets. Was the price expressed in money of account or in coined money? In domestic or foreign currency? Is it possible to relate two prices expressed in different currencies? The purpose of this paper is therefore to explore in greater depth some of the economic-monetary aspects of Renaissance Europe in order to help clarify any doubts or misreadings by building a reliable picture of the various types of currency used in Europe between the sixteenth and seventeenth centuries. This is an essential step to subsequently address the possibility of comparing prices expressed in different currencies as they emerged on different markets.